Application of ZIF-8 material in separation of C5 hydrocarbon

By using ZIF-8 materials to separate C5 hydrocarbons in steam and liquid phases, the problem of high energy consumption and insufficient identification ability in existing technology has been solved. Circulation performance.

CN119368149AActive Publication Date: 2025-01-28BEIJING UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411586410.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art has problems such as high separation energy consumption, large equipment investment, complex operation process and large solvent consumption when separating C5 hydrocarbons, and traditional adsorbent materials lack the ability to recognize molecules with subtle size differences.

Method used

The use of ZIF-8 materials to achieve the screening and separation of C5 hydrocarbon compounds in steam and liquid phases. The preparation method includes a reaction of 1: 4 with a Moore of 2-metimimidazole, which forms the ZIF-8 material , By combined with the binder CMC and activated carbon, the ZIF-8 composite material is prepared to improve the separation performance.

Benefits of technology

The efficient screening and separation of five C5 mixtures reduces separate energy consumption and equipment investment, and the ZIF-8 material has good circulating utilization performance, which can regenerate under vacuum or inert gas atmosphere.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368149A_ABST
    Figure CN119368149A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of material and chemical process research, and relates to application of a ZIF-8 material to separation of C5 hydrocarbon. The ZIF-8 material is simple in preparation steps and can be synthesized in a large scale, and green synthesis can be realized by using deionized water as a solvent. The ZIF-8 material and the composite material thereof realize purification of isoprene in a steam and liquid phase C5 mixture. The ZIF-8 material is very easy to regenerate after adsorption and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material and chemical process research, and is characterized in that it relates to the application of a ZIF-8 material in separating C5 hydrocarbons. Background Art

[0002] C5 fraction is an important chemical raw material with potential application value. The yield, composition and content of the cracking C5 fraction mainly depend on the composition of the cracking raw material. The lighter the cracking raw material, the lower the C5 yield. The C5 fraction contains more than 20 components with similar boiling points, mainly including dienes (isoprene and isoprene, etc.), monoolefins (1-pentene and 2-pentene, etc.) and alkanes (n-pentane and isopentane). Among them, isoprene has a higher utilization value and a higher content. Isoprene is mainly used to produce polyisoprene rubber with performance close to that of natural rubber. It is also the second monomer of butyl rubber and styrene-isoprene block polymer (SIS) thermoplastic elastomer. Isoprene is an extremely important C5 diene. It is an important monomer of synthetic rubber and is mainly used to synthesize isoprene rubber. Its output ranks third in synthetic rubber after styrene-butadiene rubber and butadiene rubber. In recent years, due to the rapid increase in natural rubber prices, the output of isoprene rubber has rebounded, providing opportunities for the application of isoprene in the rubber field. Isoprene can also be used as a comonomer in the synthesis of butyl rubber to improve the vulcanization properties of butyl rubber.

[0003] The C5 fraction has a complex composition, with similar boiling points and low relative volatility. It is easy to form azeotropes between the components, and the dienes are easy to polymerize. Therefore, it is difficult to separate high-purity isoprene products. The commonly used methods in industry at present are multi-step extractive distillation and azeotropic distillation to obtain polymerization-grade pure components. The methods using extractive distillation or azeotropic distillation generally have the problems of high separation energy consumption, large equipment investment, complex operation process, large solvent consumption, and environmental unfriendliness.

[0004] Adsorption separation technology is considered to be a separation technology with great potential due to its advantages such as convenient operation, economical equipment cost and low production energy consumption. Although traditional adsorption materials such as porous polymers, molecular sieves and activated carbon have been widely used in the field of adsorption separation, these materials generally have the limitations of difficult pore size control and insufficient recognition ability for molecules with subtle size differences.

[0005] Metal-organic framework materials have been widely used in the research field of adsorption and separation of low-carbon hydrocarbons. In recent years, many studies have reported the adsorption and separation of gaseous hydrocarbons such as ethylene / ethane, propylene / propane, and the adsorption and separation of liquid hydrocarbons such as C6-C8 has also been very mature, but there are very few studies on C5 compounds. For example, Michael Maes et al. first reported the selective adsorption and separation of cis / trans-isopentadiene using MIL-96, chabazite and 5A molecular sieves, but the adsorption separation selectivity was not high. Huabin Xing et al. used ion hybrid microporous materials ZU-62 and TIFSIX-2-Cu-i for the separation of isoprene. Although the regeneration performance of the material is good, it still has a large adsorption amount of isoprene at 0.1 bar (298k), which cannot achieve the screening effect and the separation selectivity is not high. Zongbi Bao's research group used zeolite 5A and gallic acid MOF in combination to achieve the separation of C5 dienes. Although the study has a high selectivity, it cannot achieve one-step separation.

[0006] Therefore, it is of great research significance to develop new separation materials and separation methods for the separation application of metal-organic framework materials in multi-component C5 hydrocarbons, and to realize the screening separation of a five-component mixed system of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane. Summary of the invention

[0007] Based on the research in this field, the present invention provides an application of a ZIF-8 material in separating five C5 hydrocarbons, specifically involving the use of the ZIF-8 material to achieve the screening of C5 hydrocarbons in steam and liquid phase separation.

[0008] The present invention is achieved through the following technical solutions: The present invention provides a method for preparing a crystalline ZIF-8 material, comprising the following steps: Dissolve zinc nitrate hexahydrate in methanol to form a transparent solution A; dissolve 2-methylimidazole (2-MIm) in methanol to form a transparent solution B; then pour the transparent solution B into the transparent solution A; stir the mixed solution at room temperature for 6-30 hours at a speed of 500-1000 rpm, and then stand for 1-24 hours; centrifuge and wash with methanol several times, and then dry at 50-100°C.

[0009] Furthermore, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4; the amount of methanol added to the transparent solution A is 0.01 mmol Zn(NO3)2·6H2O corresponding to 75 mL methanol; and the volume ratio of methanol in the transparent solution A and the transparent solution B is 1:1.

[0010] The present invention also provides a green large-scale preparation method of ZIF-8 material, comprising the following steps: dissolving zinc acetate dihydrate and 2-methylimidazole in deionized water respectively to form two clear solutions respectively; then quickly pouring the zinc acetate dihydrate solution into the 2-methylimidazole solution, rapidly stirring for 30 minutes, and standing for 24 hours; after centrifugation, washing three times with methanol, and then soaking in methanol for 48 hours, during which time it is replaced with fresh methanol 3-6 times, and vacuum drying at 100°C to obtain ZIF-8 material.

[0011] Furthermore, the molar ratio of zinc acetate dihydrate to 2-methylimidazole is 1:8, the amount of deionized water added when preparing zinc acetate dihydrate is limited to 0.34 mol zinc acetate dihydrate corresponding to 1.8 L deionized water, and the volume ratio of deionized water in the two clear solutions is 1:1.

[0012] Furthermore, the ZIF-8 material activation method is to heat the sample under vacuum, and the vacuum drying temperature is 30-120° C. and the time is 6-24 hours.

[0013] The present invention also provides application of the ZIF-8 material in separating C5 hydrocarbons.

[0014] Furthermore, the C5 hydrocarbons include isoprene and at least one of 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane.

[0015] Furthermore, the ZIF-8 material achieves the screening of C5 hydrocarbon vapor and liquid.

[0016] Furthermore, the ZIF-8 material can be recycled, and the regeneration method is to heat the ZIF-8 material to 30-120° C. under vacuum or inert gas atmosphere conditions and maintain it for 6-24 hours, wherein the inert gas is nitrogen or helium.

[0017] The present invention also provides an application of a ZIF-8 composite material in separating five C5 hydrocarbons.

[0018] Furthermore, the preparation method of the ZIF-8 composite material is to add a binder CMC and activated carbon to a dried ZIF-8 material sample, and obtain ZIF-8 composite material particles by extrusion molding. The content of the binder CMC is 0.5%-30%, and the content of the activated carbon is 0%-30%.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0020] (1) The ZIF-8 material has simple preparation steps, can be synthesized on a large scale, and can be synthesized greenly by using deionized water as a solvent. The MOF material can be combined with a binder and extruded into a composite material. The obtained composite material overcomes the shortcomings of powdered adsorbent blocking the pipeline and being difficult to recycle. The ZIF-8 material prepared by the green large-scale method and the composite material prepared by combining ZIF-8 and a binder both show similar screening effects.

[0021] (2) The ZIF-8 material and its composite material achieved the screening separation of five C5 mixtures.

[0022] (3) The ZIF-8 material can be used for the purification of isoprene in vapor and liquid phases.

[0023] (4) The ZIF-8 material is very easy to regenerate after adsorption and can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Powder X-ray diffraction (PXRD) patterns of ZIF-8 crystal samples, green large-scale synthetic samples and simulations.

[0025] Figure 2 This is the N2 adsorption isotherm of ZIF-8 material at 77 K.

[0026] Figure 3 Schematic diagram of the fixed penetration device.

[0027] Figure 4 Fixed-bed penetration diagram of ZIF-8 material bubbled at 273 K and tested at 298 K.

[0028] Figure 5 The adsorption isotherms of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 298 K.

[0029] Figure 6 The adsorption isotherms of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 308 K.

[0030] Figure 7 The adsorption isotherms of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 318 K.

[0031] Figure 8 This is a diagram of the adsorption rate test device.

[0032] Fig. 9The adsorption rate curves of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 298 K.

[0033] Fig.10 The adsorption rate curves of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 308 K.

[0034] Fig.11 The adsorption rate curves of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 material at 318 K.

[0035] Fig.12 Figure 5 shows the fixed bed penetration cycle of ZIF-8 material bubbling at 273 K.

[0036] Fig.13 This is a graph showing the changes in concentration of various components of ZIF-8 material in the liquid phase adsorption experiment.

[0037] Fig.14 3 and 4 are N2 adsorption isotherms of the ZIF-8 composite material after extrusion molding at 77 K.

[0038] Fig.15 This is the adsorption rate curve of isoprene and n-pentane of ZIF-8 / CMC2 prepared in Example 3 at 298 K.

[0039] Fig.16 This is the adsorption rate curve of isoprene and n-pentane of ZIF-8 / CMC2-AC1 prepared in Example 4 at 298 K.

[0040] Fig.17 This is the fixed bed penetration diagram of ZIF-8 / CMC2 prepared in Example 3, bubbled at 273 K and tested at 298 K.

[0041] Fig.18 This is the fixed bed penetration diagram of ZIF-8 / CMC2-AC1 prepared in Example 4, bubbled at 273 K and tested at 298 K.

[0042] Fig.19 This is a graph showing the liquid phase penetration test results of ZIF-8 / CMC2-AC1 prepared in Example 4 at 298K.

[0043] Fig. 20 This is a breakthrough curve diagram of various components in the C5 fraction simulated in industrial production. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0045] Example 1 Synthesis of ZIF-8 crystal sample Step 1: Dissolve Zn(NO3)2·6H2O (5.95 g, 0.02 mol) in 150 mL of methanol to form a clear solution A; 2-Methylimidazole (2-MeIm; 6.16 g, 0.08 mol) was dissolved in 150 mL of methanol to form a clear solution B; Then, the transparent solution B is poured into the transparent solution A; the mixed solution is stirred at room temperature for 6-30 hours at a rotation speed of 500-1000 rpm, and then allowed to stand for 1-12 hours to obtain a ZIF-8 crystal sample.

[0046] Step 2: In order to remove the solvent molecules in the pores of the ZIF-8 crystal sample, the crystal sample obtained above is washed with high-purity methanol and then immersed in a methanol solvent. The solvent exchange is continued for 3-6 times, and the exchanged crystalline sample is transferred to a fresh methanol solvent.

[0047] Example 2 Large-scale synthesis of ZIF-8 samples Step 1: Dissolve zinc acetate dihydrate (0.34 mol) and 2-methylimidazole (2.72 mol) in 1.8 L of deionized water to form two clear solutions. Then quickly pour the zinc acetate dihydrate solution into the 2-methylimidazole solution, stir rapidly for 30 minutes, and let stand for 24 hours.

[0048] Step 2: In order to remove the solvent molecules in the pores of the ZIF-8 sample material, the ZIF-8 sample obtained above was washed with high-purity methanol and then immersed in a methanol solvent. The solvent exchange was continued for 3-6 times. The exchanged ZIF-8 sample was transferred to a fresh methanol solvent.

[0049] Powder X-ray Diffraction Characterization Test The ZIF-8 samples prepared in Example 1 and Example 2 were subjected to powder X-ray diffraction characterization test. The test results are as follows: Figure 1 It can be seen that the PXRD of ZIF-8 and ZIF-8-H2O synthesized in methanol or deionized water is consistent with each peak of the XRD of simulated ZIF-8, indicating that both methods can successfully prepare ZIF-8 samples, that is, ZIF-8 samples have been successfully synthesized.

[0050] Separation performance test Before the adsorption isotherm test, the methanol suspension of the sample in the second step of Example 1 and Example 2 was centrifuged at 5000 rpm for 5 minutes, the supernatant was discarded, and the material was degassed at 80°C for 12 hours to obtain a dry sample of the desolventized material. 50-100 mg of the dry sample was placed in an adsorption tube and connected to the adsorption instrument for adsorption isotherm test.

[0051] (1) Nitrogen adsorption test Before the test, vacuum degassing was performed first, and after the degassing was completed, nitrogen adsorption was tested at 77K. The test results of the samples obtained in Example 1 and Example 2 were the same, see Figure 2 , the material shows a reversible typical type I N2 adsorption isotherm with closed adsorption and desorption branches and no hysteresis, indicating its intrinsic microporosity characteristics.

[0052] (2) Adsorption isotherm test of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane The test results of the samples obtained in Example 1 and Example 2 are the same. Figure 5-7 , Figure 5 , Figure 6 , Figure 7 The adsorption isotherms of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane at 298 K, 308 K and 318 K for the samples obtained in Example 1 and Example 2. At 298 K and 0.1 bar, the adsorption amount of isoprene by ZIF-8 is 0.01 mmol / g, while the adsorption amounts of 1-pentene, trans-2-pentene, cis-2-pentene and n-pentane are 3.8593 mmol / g, 4.1306 mmol / g, 3.8539 mmol / g, 3.2717 mmol / g, respectively. By comparing the adsorption isotherms at different temperatures, it can be seen that the adsorption amount of isoprene is significantly lower than that of the other four molecules, indicating that the ZIF-8 sample has the potential to separate isoprene from C5 hydrocarbons.

[0053] (3) Fixed bed penetration test of mixed isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane (v / v / v / v / v=1 / 1 / 1 / 1 / 1) Before the penetration test, the methanol suspension of the sample in the second step of Example 1 and Example 2 was centrifuged at 5000 rpm for 5 minutes, the supernatant was discarded, and the material was degassed at 80°C for 12 hours to obtain a dry sample of the desolvated material. 300-1000 mg of the desolvated dry sample was loaded into the penetration column and connected to the penetration device for testing ( Figure 3 The penetration test results of the samples obtained in Example 1 and Example 2 are the same (see Figure 4 ), Figure 4 This is the fixed bed penetration diagram of ZIF-8 material bubbling at 273 K and tested at 298 K. The calculation results show that when the mixed steam passes through the ZIF-8 material and penetrates the column, the signal of isoprene is immediately detected at the outlet, and the dynamic adsorption amounts of 1-pentene, trans-2-pentene, cis-2-pentene and n-pentane are 1.25 mmol / g, 1.11 mmol / g, 1.12 mmol / g, and 1.05 mmol / g, respectively.

[0054] The recycling of adsorbents is of great significance in practical industrial applications. In order to prove the recyclability of ZIF-8 materials for the separation of C5 compounds, the fixed bed penetration experiment was carried out 5 times in succession. The regeneration method of ZIF-8 material is to heat the ZIF-8 material to 30-120°C under vacuum or inert gas atmosphere for 6-24 hours, and the inert gas is nitrogen or helium. Fig.12 As shown, the retention time of the adsorbents for C5 hydrocarbons is almost the same, indicating that ZIF-8 has good cycling performance and regeneration ability.

[0055] Adsorption rate test Before the adsorption rate test, the methanol suspension of the samples in the second step of Example 1 and Example 2 was centrifuged at 5000 rpm for 5 minutes, the supernatant was discarded, and the material was dried in an oven at 60°C for 6 hours to obtain a desolventized dry sample. 3-8 mg of the powder was placed in a crucible and the adsorption rate test was performed using a device modified from a thermogravimetric analyzer ( Figure 8 ).

[0056] The adsorption rate test results of the samples obtained in Example 1 and Example 2 are the same (see Figure 9-11 ), Fig. 9 , Fig.10 and Fig.11 The adsorption rate curves of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane on ZIF-8 samples at 298 K, 308 K and 318 K. By comparison, it was found that under dynamic conditions, ZIF-8 reached equilibrium with 1-pentene, cis / trans-2-pentene and n-pentane within 10 minutes, while isoprene was hardly adsorbed, indicating that isoprene could not enter the pores of ZIF-8 under dynamic conditions.

[0057] Liquid phase adsorption experiment In order to demonstrate the practicality of ZIF-8, a liquid phase adsorption experiment was conducted on the ZIF-8 samples obtained in Example 1 and Example 2. The specific operation was as follows: 25 mg of activated ZIF-8 was added to a 1.5 mL liquid chromatography bottle, followed by 1 mL of liquid isoprene, and 4 µL of 1-pentene, cis-2-pentene, trans-2-pentene, and n-pentane. Using a microsyringe, 3 μL of liquid was sampled every hour for gas chromatography testing. The content of C5 hydrocarbons was determined by analyzing the peak areas at different retention times. The results are shown in Table 1. Fig.13 , Fig.13 This is a graph showing the concentration changes of various components in the liquid phase adsorption experiment. It can be seen that ZIF-8 can be used to adsorb trace impurities in isoprene to obtain high-purity isoprene.

[0058] Example 3 Preparation of ZIF-8 composite material without added activated carbon Step 1: Dissolve zinc acetate dihydrate (0.34 mmol) and 2-methylimidazole (2.72 mmol) in 1.8 L of deionized water to form two clear solutions respectively; then quickly pour the zinc acetate dihydrate solution into the 2-methylimidazole solution, stir rapidly for 15 minutes, and let stand for 24 hours.

[0059] Step 2: In order to remove the solvent molecules in the material pores, the crystalline sample obtained above is washed with high-purity methanol and then immersed in a methanol solvent. The solvent exchange is continued for 3-6 times. The exchanged crystalline sample is transferred to a fresh methanol solvent.

[0060] Step 3: Centrifuge the methanol suspension of the sample in step 2 at 5000 rpm for 5 minutes, discard the supernatant, and degas at 80 °C for 12 hours to obtain a dry sample of the material with solvent removed; Step 4: Take 1 g of the dry sample obtained in the third step, add 20 mg of CMC, mix well, and then slowly add 1.2 mL of deionized water while stirring to obtain a paste before molding.

[0061] Step 5: The paste from step 4 was extruded into strips with a diameter of 3 mm, and then extruded into small balls with a diameter of 3 mm (ZIF-8 / CMC2) through an instrument, and dried in an oven at 80 °C for 3 h.

[0062] Example 4 Preparation of ZIF-8 composite material with added activated carbon Step 1: Dissolve zinc acetate dihydrate (0.34 mmol) and 2-methylimidazole (2.72 mmol) in 1.8 L of deionized water to form two clear solutions respectively; then quickly pour the zinc acetate dihydrate solution into the 2-methylimidazole solution, stir rapidly for 15 minutes, and let stand for 24 hours.

[0063] Step 2: In order to remove the solvent molecules in the material pores, the crystalline sample obtained above is washed with high-purity methanol and then immersed in a methanol solvent. The solvent exchange is continued for 3-6 times. The exchanged crystalline sample is transferred to a fresh methanol solvent.

[0064] Step 3: Centrifuge the methanol suspension of the sample in step 2 at 5000 rpm for 5 minutes, discard the supernatant, and degas at 80 °C for 12 hours to obtain a dry sample of the material with solvent removed; Step 4: Take 1 g of the sample obtained in the third step, add 20 mg of CMC and 10 mg of activated carbon, mix well, and then slowly add 1.2 mL of deionized water while stirring to obtain a paste before molding.

[0065] Step 5: The paste from step 4 was extruded into strips with a diameter of 3 mm, and then extruded into small balls with a diameter of 3 mm (ZIF-8 / CMC2-AC1) through an instrument and dried in an oven at 80 °C for 3 h.

[0066] Example 5 Step 1: Dissolve zinc acetate dihydrate (0.34 mmol) and 2-methylimidazole (2.72 mmol) in 1.8 L of deionized water to form two clear solutions respectively; then quickly pour the zinc acetate dihydrate solution into the 2-methylimidazole solution, stir rapidly for 30 minutes, and let stand for 24 hours.

[0067] Step 2: In order to remove the solvent molecules in the material pores, the crystalline sample obtained above is washed with high-purity methanol and then immersed in a methanol solvent. The solvent exchange is continued for 3-6 times. The exchanged crystalline sample is transferred to a fresh methanol solvent.

[0068] Step 3: Centrifuge the methanol suspension of the sample in the second step at 5000 rpm for 5 minutes, pour off the supernatant, and dry it in an oven at 60°C for 6 hours to obtain a dry sample of the material with solvent removed.

[0069] Step 4: Take 200 g of the sample obtained in the third step, add 20 g of CMC and 10 g of activated carbon, mix well, and then slowly add 50 mL of deionized water while stirring to obtain a paste before molding.

[0070] Step 5: The paste from step 4 was extruded into strips with a diameter of 3 mm, and then extruded into small balls with a diameter of 3 mm (ZIF-8 / CMC2-AC1), and dried in an oven at 80 °C for 3 h.

[0071] Example 6 The difference between Example 6 and Example 4 is: Step 4: Take 100 g of the sample obtained in the third step, add 20 g of CMC and 10 g of activated carbon, mix well, and then slowly add 50 mL of deionized water while stirring to obtain a paste before molding.

[0072] The remaining steps are all the same.

[0073] Example 7 The difference between Example 7 and Example 4 is: Step 4: Take 100 g of the sample obtained in the third step, add 0.5 g of CMC and 30 g of activated carbon, mix well, and then slowly add 50 mL of deionized water while stirring to obtain a paste before molding.

[0074] The remaining steps are all the same.

[0075] The performance test results for C5 hydrocarbons obtained in Examples 5-7 are the same as those in Example 4.

[0076] Nitrogen adsorption test The extruded ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 pellets prepared in Example 3 and Example 4 were subjected to nitrogen adsorption test. Before the test, vacuum degassing was performed. After the degassing was completed, nitrogen adsorption was tested at 77 K. The results are shown in FIG. Fig.14 , Fig.14 Figure 2 is the N2 adsorption isotherms of ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 after extrusion molding at 77 K. The results show that the N2 adsorption of ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 did not decrease significantly, indicating that ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 still maintain the inherent microporosity characteristics after molding.

[0077] Adsorption rate test The extruded ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 pellets prepared in Example 3 and Example 4 were tested for adsorption rate using a device modified from a thermogravimetric analyzer. The activation step was achieved by heating to 100°C on the thermogravimetric analyzer and purging with N2 for 30 min. The results are shown in Figure 15-16 , Fig.15 The adsorption rate curves of isoprene and n-pentane of ZIF-8 / CMC2 at 298 K. It can be seen that compared with the pure ZIF-8 material, the adsorption rate of ZIF-8 / CMC2 is significantly reduced, and the adsorption amount is not significantly reduced, indicating that the mass transfer performance of the ZIF-8 composite material is reduced after molding. Fig.16The adsorption rate curves of isoprene and n-pentane on ZIF-8 / CMC2-AC1 at 298 K. The adsorption rate of ZIF-8 / CMC2-AC1 is almost the same as that of ZIF-8 powder. This proves that the addition of activated carbon can increase the mass transfer rate.

[0078] Dynamic penetration test The ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 sample pellets prepared in Example 3 and Example 4 were placed in a test tube and dried under vacuum at 100 °C for 12 h. In order to verify the actual C5 separation performance of the synthesized materials, a dynamic penetration experiment was carried out by bubbling a mixture of isoprene / 1-pentene / cis-2-pentene / trans-2-pentene / n-pentane (1 / 1 / 1 / 1 / 1, v / v / v / v / v) at 0 °C. The results are shown in Fig.17 and Fig.18 , Fig.17 and Fig.18 The fixed bed penetration diagrams of ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1 prepared in Example 3 and Example 4, respectively, at 273 K bubbling and tested at 298 K. It can be seen from the penetration curve that isoprene will immediately pass through the penetration columns of ZIF-8 / CMC2 and ZIF-8 / CMC2-AC1, while the retention time of 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane in ZIF-8 / CMC2 is significantly reduced compared with the ZIF-8 powder penetration column. In the penetration column of ZIF-8 / CMC2-AC1, the retention time of 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane is slightly greater than that of ZIF-8 powder penetration column, which is because the addition of activated carbon will also have a trace adsorption of isoprene, 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane.

[0079] Liquid penetration experiment Take the ZIF-8 / CMC2-AC1 prepared in Example 4, dry it in a vacuum drying oven at 100°C for 12 h, and then quickly transfer it to a liquid phase penetration column. Use a digital pump to pass the five C5 mixtures through the penetration column at a flow rate of 10 ml / min. After the liquid flows out of the upper end of the penetration column, take a sample every 3 minutes, and use a micro syringe to take 3 μL of liquid to determine the content of each C5 hydrocarbon in the outflowing liquid. The results are shown in Fig.19 , Fig.19 The figure shows the results of the liquid phase penetration experiment of ZIF-8 / CMC2-AC1 at 298 K. According to calculations, 750 ml of pure isoprene can be obtained in one liquid phase penetration.

[0080] Practical application test The ratio of the C5 fraction in industry is isoprene / 1-pentene / cis-2-pentene / trans-2-pentene / n-pentane = 28.71 / 4.20 / 3.09 / 1.70 / 8.76 (w% / w% / w% / w% / w%). At room temperature, dry N2 was added to the mixed C5 (isoprene / 1-pentene / cis-2-pentene / trans-2-pentene / n-pentane = 28.71 / 4.20 / 3.09 / 1.70 / 8.76 (w% / w% / w% / w% / w%), 30 mL in total) at a rate of 20 mL / min to form a mixed C5 gas. 24.8977 g of ZIF-8 / CMC2-AC1 prepared in Example 4 was taken, and the breakthrough curve of the C5 mixture was measured at 298 K. The outlet gas of the column was monitored using a gas chromatograph and a flame ionization detector (FID). -1 The sample was regenerated at a N2 flow rate of 6 h. Fig. 20 As shown in the figure, after integral calculation, 2.81 mmol / g of pure isoprene can be obtained in one fixed bed breakthrough experiment.

[0081] From the above analysis, it can be seen that ZIF-8 has the ability to purify isoprene. ZIF-8 exhibits high-performance adsorption capacity for 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane, while the adsorption amount of isoprene is negligible. In addition, ZIF-8 also has excellent recycling performance.

Claims

1. Application of ZIF-8 material in separation of C5 hydrocarbons.

2. The application of the ZIF-8 material according to claim 1 in separating C5 hydrocarbons, characterized in that: The C5 hydrocarbons include isoprene and at least one of 1-pentene, cis-2-pentene, trans-2-pentene and n-pentane.

3. The application of the ZIF-8 material according to claim 2 in separating C5 hydrocarbons, characterized in that: The ZIF-8 material achieves the separation of C5 hydrocarbon vapor and liquid.

4. The application of the ZIF-8 material according to claim 2 in separation of C5 hydrocarbons, characterized in that: The ZIF-8 material can be recycled, and the regeneration method is to heat the ZIF-8 material to 30-120° C. under vacuum or inert gas atmosphere conditions and keep it for 6-24 hours, wherein the inert gas is nitrogen or helium.

5. The use of the ZIF-8 material according to claim 2 in separating C5 hydrocarbons, characterized in that: The method for preparing the crystalline ZIF-8 material comprises the following steps: Dissolve zinc nitrate hexahydrate in methanol to form a transparent solution A; dissolve 2-methylimidazole in methanol to form a transparent solution B; then pour the transparent solution B into the transparent solution A; stir the mixed solution at room temperature for 6-30 hours at a speed of 500-1000 rpm, and then stand for 1-12 hours; centrifuge and wash with methanol several times, and then dry at 50-100°C; The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:4; the amount of methanol added to the transparent solution A is 0.01 mmol Zn(NO3)2·6H2O corresponding to 75 mL methanol; the volume ratio of methanol in the transparent solution A and the transparent solution B is 1:

1.

6. The use of the ZIF-8 material according to claim 2 in separating C5 hydrocarbons, characterized in that: The green large-scale preparation method of the ZIF-8 material is characterized by comprising the following steps: dissolving zinc acetate dihydrate and 2-methylimidazole in deionized water to form two clear solutions respectively; then quickly pouring the zinc acetate dihydrate solution into the 2-methylimidazole solution, rapidly stirring for 5 minutes, and standing for 12 hours; after centrifugation, washing with methanol three times, and then soaking in methanol for 48 hours, during which time it is replaced with fresh methanol 3-6 times, and vacuum drying at 100° C. to obtain the ZIF-8 material; The molar ratio of zinc acetate dihydrate to 2-methylimidazole is 1:

8. The amount of deionized water added when preparing zinc acetate dihydrate is limited to 0.11 mol of zinc acetate dihydrate corresponding to 1 L of deionized water. The volume ratio of deionized water in the two clear solutions is 1:

1.

7. A ZIF-8 composite material, characterized in that: The composite material comprises the ZIF-8 material according to any one of claims 1 to 6, and further comprises a binder CMC and activated carbon.

8. The ZIF-8 composite material according to claim 7, characterized in that: The content of binder CMC in the composite material is 0.5%-30%, the content of activated carbon is 0%-30%, and the rest is ZIF-8 material.

9. Use of the ZIF-8 composite material as claimed in claim 8 in separating five C5 hydrocarbons.

Citation Information

Patent Citations

  • CTMAB@ZIF-8 (Cetyl Trimethyl Ammonium Bromide@Zeolite Imidazolate Framework-8) compound adsorbent and preparation method thereof

    CN106268650A

  • Novel ZIF-8 material as well as preparation method and application thereof

    CN113402719A

  • Porous carbon foam / metal organic framework composite adsorbent for separating C6 alkane isomer as well as preparation method and application of porous carbon foam / metal organic framework composite adsorbent

    CN116532082A

  • ZIF-8 adsorbent as well as preparation method and application thereof

    CN117680102A

  • Separation of methane from higher carbon number hydrocarbons utilizing zeolitic imidazolate framework materials

    US20090216059A1